Overcurrent relay coordination with different penetration in distributed generation - Majid Mohammed, Lina (2022)
Power distribution network is suspected to performance degrading factors alike load fluctuation which trigger the power losses. In order to substitute the losses in distribution network; known amount of power is being injected directly into load through using of distributed generators (DGs). This alternative can be used to substitute power in range of 25 to 40 percent of the respective busbar load. The integrating of DG into power system influences the protection relays stability which leads to relays miscoordination. Prolonged fault clearance time is one of the negative correspondence of relays miscoordination. The more time required to clear faults is biggest threat to distribution network safety which allows more damages of power equipments. Traditionally, heuristic algorithm such as genetic algorithm are used to optimize the relay parameters d such as dialling time TSD. In this project, we modified the standard fitness function of the genetic algorithm by integrating a new parameter into it for best optimization. The proposed algorithm is outperformed while it is applied on 6 bus distribution system.